Analysis of catch composition in Gampong Deah Raya, Syiah Kuala, Banda Aceh. Issue 1 (February 2021) - Aprilla, R M; Musfidah, A; Chaliluddin, M A; Damora, A; Rusydi, I
Abstract: Gill nets are fishing tools that are commonly found in coastal areas, one of them located in Gampong Deah Raya. Various catches caught by fishermen would most likely affect the aquatic ecosystem. Information on gillnet catches is insufficient yet the needs of the information are most urgent. This study aims to determine the composition and the size of the catch based on Fishbase literature and journals. This study has been done from January until March 2019 in Deah Raya, Syiah Kuala, Banda Aceh. The method used in this research a descriptive survey. The results of this study indicated that there were 31 species of fish caught using gill nets and the total samples obtained during the study were as many as 6048, there were 3 species that frequently captured namely Leiognathus sp., Nemipteru sp., and Selar crumenophthamus, and proper catches as many as 3, 381 or 56% and not fit to catch as many as 2, 667 or as many as 44%.